2015
DOI: 10.3109/03630269.2015.1004335
|View full text |Cite
|
Sign up to set email alerts
|

Coinheritance of Hb D-Punjab andβ-Thalassemia: Diagnosis and Implications in Prenatal Diagnosis

Abstract: Hb D-Punjab (HBB: c.364G>C) is an abnormal hemoglobin (Hb) associated with genetic risk in association with Hb S (HBB: c.20A>T). In addition, misdiagnosing homozygosis for hemizygosis may have implication for genetic risk assessment. We present the diagnostic utility of high performance liquid chromatography (HPLC) in differential diagnosis between the Hb D-Punjab homozygote and the Hb D-Punjab/β-thalassemia (β-thal) genotype. The Hb A2 level measurement may not be a reliable parameter to differentiate between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 13 publications
1
11
0
4
Order By: Relevance
“…Hb D‐Los Angeles is an asymptomatic abnormal type of hemoglobin with no clinical importance. Conversely, the presence of this Hb is an important parameter for premarital screening, leading to prenatal misdiagnosis (Bahadır, ; Belhoul, ; Das and Mashon, ). In the Denizli province, the most common abnormal hemoglobin variant is Hb D‐Los Angeles [β121(GH4) Glu→Gln] with a frequency of 57% of the total abnormal hemoglobins observed (Atalay, ).…”
mentioning
confidence: 99%
“…Hb D‐Los Angeles is an asymptomatic abnormal type of hemoglobin with no clinical importance. Conversely, the presence of this Hb is an important parameter for premarital screening, leading to prenatal misdiagnosis (Bahadır, ; Belhoul, ; Das and Mashon, ). In the Denizli province, the most common abnormal hemoglobin variant is Hb D‐Los Angeles [β121(GH4) Glu→Gln] with a frequency of 57% of the total abnormal hemoglobins observed (Atalay, ).…”
mentioning
confidence: 99%
“…Consistency with the previous study showed that cases with coinherited HbD-Punjab and β 0 -thalassemia had only mild to moderate anemia. [ 2 ] In this study, the HbA 2 level measured by HPLC was 3.2% which was in the reference ranges (<3.5%). On HPLC chromatogram, the normal (3.3%) and elevated (6.4%) HbA 2 levels had been reported in two siblings who coinherited HbD-Punjab with the same β 0 -thalassemia mutation (codon 30, AGG>ACG).…”
Section: Discussionmentioning
confidence: 53%
“…[ 1 ] HbD-Punjab is quite prevalent in Pakistan, Northwest India, China, Middle East countries, and also in many other parts of the world with the overall frequency of 0.2%–3.0%. [ 2 3 4 ] Both the heterozygote and homozygote for HbD-Punjab are clinically silent conditions. However, the coinheritance of HbD-Punjab with HbS [β6(A3) Glu→Val; HBB: C.20A>T] results in mild clinical symptoms to severe conditions with sickle cell disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations